STATISTIK, POLLING, DAN PEMAHAMAN METODOLOGI PADA TEKNIK PENELITIAN SURVAI EKONOMI ISLAM - Rizqon Halal Syah Aji (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
Statistics is a tool of survai research. There is polling in survai research. In survai research methodology, statistical techniques are used to design the sampling. In survai research, the precision factor that must always be considered is sampling error and nonsampling error. Survai is also used for economic research, including the Islamic economy. As a research tool, the statistics should always be considered carefully, how statistics used in polls and survais. As a science that emphasizes the scientific aspects, Islamic economics also use survai research to see whether Islamic economics has been able to provide a positive impact on the community of scienceDOI: